Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/app11125558
|View full text |Cite
|
Sign up to set email alerts
|

The Perception of the Online Teaching Process during the COVID-19 Pandemic for the Students of the Physical Education and Sports Domain

Abstract: The context of the COVID-19 pandemic required the implementation of special measures to ensure the continuity and quality of teaching in higher education. The study presented here aims to identify the differences of opinion between the age categories of students in the first year of the Faculty of Physical Education and Sports in Galati, Romania, regarding teaching, learning and assessment activities on online platforms. A total of 147 students divided into three age groups (under 20 years, 20–30 years and ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 43 publications
4
19
0
Order By: Relevance
“…One aspect to keep in mind is that these five teaching performance criteria refer to the didactic competencies that teachers display in their interaction with students in class or in practice, and these can be evaluated differently according to the stage of advancement in the professional training of the student being evaluated. The data from this study regarding differences by stage or academic cycle coincide with findings reported in studies on student evaluation, teaching and teacher performance in the context of higher education (Marsh and Hocevar, 1984;Kamran et al, 2012;Kalender, 2015;Müller et al, 2017;Kitto et al, 2019;Mocanu et al, 2021;Pérez-Villalobos et al, 2021). Furthermore, these differences in student perception may be related to student expectations and prior interest (van de Grift et al, 2016;Feistauer and Richter, 2018).…”
Section: Differences Among Groupssupporting
confidence: 83%
See 1 more Smart Citation
“…One aspect to keep in mind is that these five teaching performance criteria refer to the didactic competencies that teachers display in their interaction with students in class or in practice, and these can be evaluated differently according to the stage of advancement in the professional training of the student being evaluated. The data from this study regarding differences by stage or academic cycle coincide with findings reported in studies on student evaluation, teaching and teacher performance in the context of higher education (Marsh and Hocevar, 1984;Kamran et al, 2012;Kalender, 2015;Müller et al, 2017;Kitto et al, 2019;Mocanu et al, 2021;Pérez-Villalobos et al, 2021). Furthermore, these differences in student perception may be related to student expectations and prior interest (van de Grift et al, 2016;Feistauer and Richter, 2018).…”
Section: Differences Among Groupssupporting
confidence: 83%
“…A second hypothesis was the existence of significant differences in the evaluation of the didactic performance of the teacher, according to sex, age groups, and academic level (stage) of the psychology students. To date, little is known about possible differences according to the age of the student body in the appraisal of teaching in the context of University education, but differences in students' appraisal of teaching according to their level of advancement in their studies have been reported (Marsh and Hocevar, 1984;Kamran et al, 2012;Kalender, 2015;Müller et al, 2017;Kitto et al, 2019;Mocanu et al, 2021;Pérez-Villalobos et al, 2021). Similarly, differences have been reported according to the gender of the student body, with respect to the students' assessment of teaching and the performance of their teachers, in the context of higher education (Boring, 2015;Boring et al, 2016;Potvin and Hazari, 2016;Eouanzoui and Jones, 2017;Heffernan, 2021;Kreitzer and Sweet-Cushman, 2021;Valencia, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The confidence interval was set at 95% (p < 0.05). For reasons related to the multitude of data obtained from statistical processing, the present paper does not present the influence of the age variable on the opinions expressed or the centralization and interpretation of the answers to open questions, these last 2 aspects being already published in the previous study [37].…”
Section: The Statistical Analysis Of Datamentioning
confidence: 99%
“…The use of the cross-sectional design was preferred, given the various profiles of students' exposure, across different classes and study years, to the three types of teaching taken into consideration in the study. Moreover, the cross-sectional design was successfully used in previous literature on the same theme [43], including in Romania [54,55].…”
Section: Designmentioning
confidence: 99%